The Power Netizen +62 in Influence Public Opinion: Analysis of Online Debates on Social Issues - Pradanna, Satrio Alpen; Irawan, Hendri (Proceeding International Conference on Religion, Science and Education, 2024)
Information and Communication Technology has profoundly influence societal communication, with Indonesia being no exception. A striking phenomenon, labeled as "The Power Netizen +62," has surfaced, wielding considerable influence over public sentiment through online discourse on social concerns, Public opinion reflects the collective perception, beliefs, and views of society on specific issues. The influence of social media and digital information has played a crucial role in shaping and altering public opinions. This study delves into the significant role played by these engaged internet users in molding emotions and viewpoints within the digital sphere. Employing a qualitative descriptive method coupled with content analysis, the research underscores that digital denizens actively contribute to shaping resolutions for diverse social quandaries. The results of the study indicate thatprofound insights into how the dynamic involvement of these digital citizens, colloquially referred to as "The Power Netizen +62," not only molds societal viewpoints but also steers discussions, culminating in tangible impacts on communal decisions and actions. This phenomenon underscores the potent interplay between technology, active citizenship, and social change in the contemporary landscape, offering a comprehensive understanding of the evolving dynamics in the digital age.